2011
DOI: 10.1111/j.1467-9701.2011.01398.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the Border Effect an Artefact of Geographical Aggregation?

Abstract: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 35 publications
5
21
1
1
Order By: Relevance
“…Now, as in Llano‐Verduras et al. (), the contiguity dummy becomes nonsignificant for the two models, and even negative for M8.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Now, as in Llano‐Verduras et al. (), the contiguity dummy becomes nonsignificant for the two models, and even negative for M8.…”
Section: Resultssupporting
confidence: 59%
“…This persistent external border effect around 8 is slightly larger than that obtained by Llano‐Verduras et al. () with region‐to‐country [3.3 = exp(1.2)] and province‐to‐country [4.9 = exp(1.6)] data. Note that the papers use different data sets but similar specifications for distance and the same estimation procedures as in M6 and M7 .…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…This finding makes sense in light of these border provinces' past political tensions with international neighbours and their tendency to be overshadowed by other, larger Spanish provinces nearby (e.g., Girona vs. Barcelona, Guipuzcoa vs. Vizcaya, Cáceres vs. Sevilla). The previous result for border regions and the link between internal and external trade are crucial to researchers using the C-intereg dataset- Llano et al (2010); Ghemawat et al (2010); Llano-Verduras et al (2011);-Garmendia et al (2012), or the official freight flows considered in this paper, as the data show no clear sign that international transit flows are included with interprovincial flows.…”
Section: Intranational Home Bias 389mentioning
confidence: 92%
“…From this analysis we can conclude that, regardless of flow type, the bulk of trade takes place over short distances and beyond a certain point the negative effect of distance falls off deeply. Hence the relevance of territorial disaggregation, Llano‐Verduras et al () and Garmendia et al () have shown that, with insufficient territorial disaggregation of trade, the gravity equation may lead to an overestimation of the border effect and an underestimation of the distance effect. As we will see in the next section, this overall effect can arise not just when regions are used instead of provinces, but also when countries are used instead of regions.…”
Section: The Datamentioning
confidence: 99%